Assessing the feasibility of HPV screening for cervical cancer in pregnant women in Ethiopia - Mekuria, Selamawit; Assiged, Nahom; Biazin, Habtamu; Borgfeldt, Christer; Abebe, Tamrat; Mihret, Adane; Forslund, Ola; Jerkeman, Mats (Scientific Reports, 2025)
Pregnant women have historically and are currently being excluded from cervical cancer screening in most low and middle-income countries (LMICs). The aim of this study was to assess the feasibility and outcomes of including pregnant women in a HPV self-sampling-based screening program in Ethiopia. Pregnant women, recruited from a previously established cohort, were included. They answered a questionnaire and provided HPV self-samples. If the woman was HR-HPV positive, she underwent triage with VIA with or without Iodine. If positive in triage, the woman was re-scheduled after delivery for a new exam. Primary outcome was screening participation. The participation rate of pregnant women was 92.1% (117/127) (95% CI 86.0–96.1%). They had the same knowledge about cervical cancer and acceptance rate to the study as their non-pregnant peers. Pregnant women had less history of previous screening (p = 0.08). The HPV prevalence was 25.4% (29/114) in self-samples. 93.1% (27/29) attended follow-up, where only 11 had not delivered, and 54.6% (6/11) had detectable HPV infection in their cervical samples. Including pregnant women in HPV self-sampling-based screening is feasible and highly accepted. The findings support integrating pregnant women into cervical cancer screening programs in to enhance prevention and early detection efforts.